Peningkatan Motivasi Belajar Siswa Melalui Metode Diskusi Dalam Pembelajaran Pendidikan Kewarganegaraan Pada Siswa Kelas 3 SD Negeri 2 Ketandan Klaten Utara - Swasini, Asih (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The aim of this research is to reveal learning steps to increase students' learning motivation in learning Citizenship Education with the theme My Nation, My Pride, in grade 3 students at SD Negeri 2 Ketandan, North Klaten. The research subjects were 23 grade 3 students at SD Negeri 2 Ketandan, North Klaten, consisting of 15 boys and 8 girls. Data collection techniques use test techniques with Essay Questions and non-test techniques. Data research instruments were student observation sheets and questionnaire sheets. Data analysis methods use quantitative and qualitative techniques, and instrument validity uses content validity. The results of the research show that there is an increase in students' learning motivation in discussing the theme of My Indonesian Nation, which can be seen from the increase in the average score and percentage of completion of learning outcomes for each cycle. In conclusion, the use of discussion methods in the learning process through a question and answer process can increase student learning motivation, so that it can also improve student learning achievement results.